From Fragmented Facts to Unified Knowledge: Exploring Concept Mapping in Neuromuscular Physiology Among First-Year Medical Students - Shanmugarajah, Mangani Mangalavalli; Mondal, Himel; Das, Tina (Curēus (Palo Alto, CA), 2024)
Background First-year medical students may find it challenging to integrate complex physiological concepts, particularly neuromuscular physiology. While concept mapping has shown promise in medical education, its specific application in teaching intricate physiological mechanisms still needs to be explored. With this background, the objective of the study was to assess the feasibility of using concept mapping among first-year medical students and to explore the perception of students about concept mapping as an educational tool. Methods A mixed-methods study was conducted with first-year medical students (n = 110) of the 2023-2024 batch at All India Institute of Medical Sciences, Bhubaneswar, India. A briefing on the basic theories of concept mapping was carried out. Students participated in a structured concept mapping session focusing on the mechanism of muscle contraction. Students (two students in a group) created concept maps illustrating relationships between neuronal architecture, action potentials, neuromuscular transmission, sarcotubular system, excitation-contraction coupling, and muscle contraction processes. Data collection included digital submissions of concept maps and structured feedback questionnaires. Two faculty members evaluated the concept maps, and student feedback was analyzed using quantitative and qualitative approaches. Results A total of 110 first-year undergraduate medical students participated in the study and created 55 concept maps. The students scored 17.32 ± 1.7 out of 20 maximum achievable scores, which corresponds to an average of 86.59%. Seventy-five (68.18%) students rated the technique as excellent, 32 (29.09%) found it good, and only three (2.73%) rated it as average. Ninety-eight (88.8%) students strongly agreed or agreed that it provided a practical learning experience and found it refreshing compared to traditional lectures. Additionally, 102 (92.7%) students acknowledged its ability to stimulate creative thinking, and 102 (92.7%) also reported effective collaboration with peers. According to 82 (74.5%) students, concept mapping also facilitated in-depth knowledge acquisition, demonstrating its effectiveness in promoting active, engaging, and collaborative learning. Qualitative analysis revealed that concept mapping helped the students organize complex information, encourage critical thinking, improve retention through visual learning, promote collaborative knowledge-building, and facilitate self-assessment of their understanding. Conclusion Concept mapping can be used as a pedagogical tool for teaching complex neuromuscular physiology concepts to first-year medical students. The technique can bridge the gap between fragmented knowledge and integrated understanding while promoting active learning and critical thinking. The majority of the students rated it as excellent or good. It significantly enhances engagement, creative thinking, and deeper subject understanding compared to traditional lectures. Qualitative feedback underscores its role in improving comprehension of complex concepts and critical thinking skills.